Analisis Kebutuhan Pengguna Layanan Unit Layanan Bahasa FKIP Universitas Tanjungpura - Yoanna Afrimonika; Eka Fajar Rahmani (Departement of Mathematics Education, 2023)
This research aims to analyze the user needs of the Language Service Unit (LSU) at the Faculty of Teacher Training and Education, Universitas Tanjungpura. The survey method was employed, collecting data through questionnaires distributed to students and faculty members of FTTE. The findings indicate that a significant portion of respondents lacks detailed knowledge about the LSU, emphasizing the need for further awareness campaigns. User needs encompass service programs, human resource development, and training. Data analysis results reveal a high interest in language training, particularly TOEFL and HSK tests, as well as the translation services for scholarly works. The conclusion drawn from this research underscores the necessity for LSU to enhance awareness campaigns and design more targeted programs aligned with user needs. These findings provide profound insights into the challenges and opportunities for optimizing the role of LSU within FTTE, Universitas Tanjungpura. The practical implications entail the need for improved communication strategies and the development of responsive programs to meet user needs. Consequently, this research contributes to the advancement of language services in higher education environments.